2017
DOI: 10.3389/fpls.2017.00983
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen Supply on Water Stress and Recovery Mechanisms in Kentucky Bluegrass Plants

Abstract: Non-irrigated crops in temperate and irrigated crops in arid regions are exposed to an incessant series of drought stress and re-watering. Hence, quick and efficient recuperation from drought stress may be amongst the key determinants of plant drought adjustment. Efficient nitrogen (N) nutrition has the capability to assuage water stress in crops by sustaining metabolic activities even at reduced tissue water potential. This study was designed to understand the potential of proper nutrition management by study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
77
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(86 citation statements)
references
References 58 publications
8
77
1
Order By: Relevance
“…The relationship of grain yield with crop physiological traits showed that stomatal conductance could be the major determinant of the grain yield. Since global temperature and frequent occurrence of drought could maximize N losses, new avenues for improving crop productivity must thus be exploited [68][69][70][71][72].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of grain yield with crop physiological traits showed that stomatal conductance could be the major determinant of the grain yield. Since global temperature and frequent occurrence of drought could maximize N losses, new avenues for improving crop productivity must thus be exploited [68][69][70][71][72].…”
Section: Discussionmentioning
confidence: 99%
“…This might indicate that current soil test methods used do not adequately indicate the soil nutrient supply for the given soil. Optimal nutrient levels of fertilization are even more important under water deficit conditions, since reduced nutrient availability is one of the major factors limiting plant growth under drought [5,9,14]. To our knowledge, this is the first report of a comparison of maize seedling growth with N, P and K nutrient application individually or in combination under drought and well-watered conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, nutrient supply strongly affects crop productivity under drought conditions, but this is also very complex [8][9][10]. The positive effects of N and P on plant growth under drought conditions are attributed to an increase in water-use efficiency, stomatal conductance [11][12][13][14], photosynthesis and ATPase activity [5,15], as well as higher cell membrane stability and improved osmotic adjustment [16,17]. However, K increases a plant s drought tolerance through its functions in…”
Section: Introductionmentioning
confidence: 99%
“…Dry forage yield, chlorophyll content and RWC of tall fescue were found to decrease; on the contrary, the carotenoid and proline content increased under drought stress [86]. The photosynthesis, stomatal conductance, Rubisco activity, and nitrogen content of Kentucky bluegrass were severely disrupted by drought conditions [91,92]. It was reported that the activities of APX, peroxidase (POD) and glutathione peroxidase (GPX) in Kentucky bluegrass increased and then decreased with drought stress, but in desert wheatgrass (Agropyron desertorum) a continuous increase in activity of these enzymes was detected [93].…”
Section: Drought Stressmentioning
confidence: 93%